Histone H3 Lysine 9 Methyltransferase DIM5 Is Required for the Development and Virulence of Botrytis cinerea - Zhang, Xiaoli; Liu, Xinqiang; Zhao, Yanli; Cheng, Jiasen; Xie, Jiatao; Fu, Yanping; Jiang, Daohong; Chen, Tao (Frontiers in Microbiology, 2016)
Histone methylation is widely present in animals, plants and fungi, and the methylation modification of histone H3 has important biological functions. Methylation of Lys9 of histone H3 (H3K9) has been proven to regulate chromatin structure, gene silencing, transcriptional activation, plant metabolism and other processes. In this work, we investigated the functions of a H3K9 methyltransferase gene BcDIM5 in Botrytis cinerea, which contains a PreSET domain, a SET domain and a PostSET domain. Characterization of BcDIM5 knockout transformants showed that the hyphal growth rate and production of conidiophores and sclerotia were significantly reduced, while complementary transformation of BcDIM5 could restore the phenotypes to the levels of wild type. Pathogenicity assays revealed that BcDIM5 was essential for full virulence of B. cinerea. BcDIM5 knockout transformants exhibited decreased virulence, down-regulated expression of some pathogenic genes and drastically decreased H3K9 trimethylation level. However, knockout transformants of other two genes heterochromatin protein 1 (HP1) BcHP1 and DNA methyltransferase (DIM2) BcDIM2 did not exhibit significant change in the growth phenotype and virulence compared with the wild type. Our results indicate that H3K9 methyltransferase BcDIM5 is required for H3K9 trimethylation to regulate the development and virulence of B. cinerea.